Pengaruh GCG dan ERMTerhadap Kinerja Perusaaan Berbasis BSC - Amanda Sri Ningrum; Darya Setia Nugraha (Indonesian Accounting Literacy Journal, 2022)
This research aims to examine how big the significant influence of Good Corporate Governance and Enterprise Risk Management on Company Performance at PT Pos Indonesia (Persero) on Bandung City. The source of data in this study is primary data with the method of collecting data through closed questionnaires distributed to 34 respondents. The research method used is a quantitative method with the data analysis technique used is path analysis using the Statistical Package for Social Sciences (SPSS) version 26 software. The results of this study indicate that simultaneously GCG and ERM have a positive and significant effect on the performance of PT Pos Indonesia (Persero) which is 38.7%.